Discovery of microRNAs associated with the antiviral immune response of Atlantic cod macrophages. (January 2018) - Eslamloo, Khalil; Inkpen, Sabrina M.; Rise, Matthew L.; Andreassen, Rune
Highlights: This is the first report on miRNAs involved in antiviral responses of Atlantic cod. miR-731-3p and miR-462-3p are co-upregulated by viral mimic in cod macrophages. Results support hypothesis on conserved immune roles of miRNA-462/731 in teleosts. miR-2188-3p is a late pIC-responsive miRNA in cod macrophages. Some identified miRNAs were predicted to target immune-related genes in cod. Abstract: MicroRNAs (miRNAs) are known to play important immunoregulatory roles in teleosts, although miRNAs involved in the antiviral immune response of Atlantic cod ( Gadus morhua ) were previously uncharacterised. Using deep sequencing and qPCR, the present study was conducted to identify miRNAs responsive to the viral mimic, polyriboinosinic polyribocytidylic acid (pIC) in Atlantic cod macrophages. Macrophage samples isolated from Atlantic cod ( n  = 3) and treated with pIC or phosphate buffered saline (PBS control) for 24 and 72 h were used for miRNA profiling. Following deep sequencing, DESeq2 analyses identified four (miR-731-3p, miR-125b-3-3p, miR-150-3p and miR-462-3p) and two (miR-2188-3p and miR-462-3p) significantly differentially expressed miRNAs at 24 and 72 h post-stimulation (HPS), respectively. Sequencing-identified miRNAs were subjected to qPCR validation using a larger number of biological replicates ( n  = 6) exposed to pIC or PBS over time (i.e. 12, 24, 48 and 72 HPS). As in sequencing, miR-731-3p, miR-462-3p and miR-2188-3p showed significant up-regulation by pIC. The sequencing results were not qPCR-validated for miR-125b-3-3p and miR-150-3p as up- and down-regulated miRNAs at 24 HPS, respectively; however, qPCR results showed significant up-regulation in response to pIC stimulation at later time points (i.e. 48 and/or 72 HPS). We also used qPCR to assess the expression of other miRNAs that were previously shown as immune responsive in other vertebrates. qPCR results at 48 and/or 72 HPS revealed that miR-128-3-5p, miR-214-1-5p and miR-451-3p were induced by pIC, whereas miR-30b-3p and miR-199-1-3p expression were repressed in response to pIC. The present study identified ten pIC-stimulated miRNAs, suggesting them as important in antiviral immune responses of Atlantic cod macrophages. Some pIC-responsive miRNAs identified in this study were predicted to target putative immune-related genes of Atlantic cod (e.g. miR-30b-3p targeting herc4 ), although the regulatory functions of these miRNAs need to be validated by future studies.